2021
DOI: 10.18332/pne/144485
|View full text |Cite
|
Sign up to set email alerts
|

Budesonide/formoterol via the Elpenhaler® device in asthmatic patients: A real-world effectiveness study (The BOREAS Study)

Abstract: INTRODUCTION Very limited real-world data have been captured in the Greek asthmatic population regarding the effects of treatment with a fixeddose combination of budesonide/formoterol via the Elpenhaler® device, on the course of the disease and its impact on the patients' quality of life score. METHODS In this multicenter, observational study, 1230 adult asthmatic patients in Greece that had been recently prescribed a fixed-dose combination budesonide/formoterol, Elpenhaler® were enrolled. The primary endpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The features praised about the Elpenhaler device were: ease in learning and keep using the inhaler, verification of dose delivery, as well as factors related to size, weight, cleanliness and unobtrusiveness in everyday activities. In the recently published BOREAS study [ 30 ], the authors present some important clinical insights regarding the real-life effectiveness of FDC budesonide/formoterol via the Elpenhaler device in 1230 asthmatic patients. Specifically, the authors reported significant improvements in asthma control (based on ACQ-7) and quality of life (Mini AQLQ) at 3 months that were sustained after 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…The features praised about the Elpenhaler device were: ease in learning and keep using the inhaler, verification of dose delivery, as well as factors related to size, weight, cleanliness and unobtrusiveness in everyday activities. In the recently published BOREAS study [ 30 ], the authors present some important clinical insights regarding the real-life effectiveness of FDC budesonide/formoterol via the Elpenhaler device in 1230 asthmatic patients. Specifically, the authors reported significant improvements in asthma control (based on ACQ-7) and quality of life (Mini AQLQ) at 3 months that were sustained after 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Patient satisfaction with the inhaler device is one of the factors affecting the adherence of patients to treatment. In this perspective, the role of the Elpenhaler® device has been evaluated in a Greek population diagnosed with COPD and asthma [28, 29]. As far as adherence is concerned, the Elpenhaler® device, when compared with other frequently used inhalation devices, exhibited the lowest error rates for critical errors in the inhalation maneuver [30].…”
Section: Discussionmentioning
confidence: 99%
“…Combining the negative effects of smoking on asthma symptoms and exacerbations, which are the two aspects assessed to rate the control and the severity of the disease, it becomes clear that asthmatic smokers usually have more severe and uncontrolled disease and thus display a need to intensify treatment. A small number of real-life trials have shown that the main treatment options used in asthma patients remain effective in smokers, as shown in Table 1 [ 89 , 90 ]. ICS is the mainstay controller medication in asthmatic smokers, but patients might require higher doses due to the relative resistance they display.…”
Section: Prognostic and Treatment Implications In Asthmatic Smokersmentioning
confidence: 99%